Successful use of the 308-nm excimer laser in early patch stage mycosis fungoides. - Armenta, Andrew Michael; Jones, Krystal; Reichenberg, Jason S. (Journal of Lasers in Medical Sciences, 2019)
Introduction: Mycosis fungoides (MF), a type of cutaneous T-cell lymphoma, is a rare condition with a variety of treatment options. A frequently utilized method in the treatment of early-stage MF is phototherapy. Full body phototherapy can be associated with photoaging of the skin and an increased risk of developing skin cancer. Targeted phototherapy, with a 308-nm excimer laser, may be just as effective and of a lower risk. This makes it especially useful in the treatment of patients with dysplastic nevi (DN) or other conditions which can put them at a higher risk of developing skin cancer. There are currently limited data on the treatment of early-stage MF with an excimer laser. Case Report: This study reports on a 43-year-old female patient presented to the clinic with early-stage (Ia) MF. Given her history of DN, she wished to pursue targeted phototherapy with an excimer laser. Localized light treatment was performed via a 308-nm excimer laser, 3 times weekly, for a total of 17 treatments to affected lesions. Following excimer laser treatment, she had a clinical resolution of her patches. On the follow-up clinic visits, she maintained her excellent response 12 months out. Conclusion: Targeted phototherapy with a 308-nm excimer laser may be a safer and equally effective alternative to generalized phototherapy in the treatment of early-stage MF. This case report demonstrates its efficacy and advantages over traditional generalized phototherapy.